Lateral-Expansion Pharyngoplasty: Combined Technique for the Treatment of Obstructive Sleep Apnea Syndrome - Pinto,José Antonio (2020)
Abstract Introduction Obstructive sleep apnea syndrome (OSAS) is a multifactorial disease characterized by episodes of partial or complete collapse during sleep of different regions of the upper airway. Surgery for OSAS evolved with the introduction of different techniques, considering new surgical concept of reconstruction of the upper airway. Objective To retrospectively evaluate the effectiveness of a new approach aimed at reducing pharyngeal collapse by combining two surgical techniques: lateral and expansion pharyngoplasty. Methods We reviewed the medical records of 38 patients with OSAS undergoing lateral/expansion pharyngoplasty from January 2012 to December 2016. The following data were collected: patient age, gender, and pre- and postoperative body mass index (BMI), Epworth sleepiness scale (ESS) scores, snoring visual analogue scale (VAS) scores, and polysomnography (PSG) results. Results The PSG results showed a signiﬁcant reduction in the apnea/hypopnea index (AHI) from 22.4 ± 27.3 events/h preoperatively to 13.6 ± 17.9 events/h postoperatively (p = 0.009), with postoperative AHI reduction greater than 50% in 63.2% of the patients. There was also a signiﬁcant reduction in the microarousal index (19.5 ± 22.6 vs 11.0 ± 13.4 events/h; p = 0.001) and in the minimum oxygen saturation (82.6 ± 10.3 vs 86.9 ± 11.1; p = 0.007). Conclusions Lateral-expansion pharyngoplasty represents a new surgical strategy for the treatment of OSAS in patients with palatal collapse by combining two different techniques: lateral and expansion pharyngoplasty. The two techniques, performed as a one-stage procedure, led to improvements in excessive daytime sleepiness, snoring, and PSG respiratory parameters by acting on lateral and retropalatal collapse, produc- ing favorable results with good applicability in otolaryngology clinical practice.